Cancer stem cell‐targeted therapeutic approaches for overcoming trastuzumab resistance in HER2‐positive breast cancer. (20th April 2021) - Qiu, Yan; Yang, Libo; Liu, Honghong; Luo, Xiaobo
Abstract: Application of the anti‐HER2 drug trastuzumab has significantly improved the prognosis of patients with the HER2‐positive subtype of breast cancer. However, 50% of patients with HER2 amplification relapse due to trastuzumab resistance. Accumulating evidence indicates that breast cancer is driven by a small subset of cancer‐initiating cells or breast cancer stem cells (BCSCs), which have the capacity to self‐renew and differentiate to regenerate the tumor cell hierarchy. Increasing data suggest that BCSCs are resistant to conventional therapy, including chemotherapy, radiotherapy, and endocrine therapy, which drives distant metastasis and breast cancer relapse. In recent years, the trastuzumab resistance of breast cancer has been closely related to the prevalence of BCSCs. Here, our primary focus is to discuss the role of epithelial‐mesenchymal transition (EMT) of BCSCs in the setting of trastuzumab resistance and approaches of reducing or eradicating BCSCs in HER2‐positive breast cancer. Abstract : Several reported targeted therapies against breast cancer stem cells (BCSCs) to overcome trastuzumab resistance in HER2‐positive breast cancer.